Unveiling the potential applications of buds of Lonicera japonica Thunb. var. chinensis (Wats.) Bak based on in vitro biological activities, bio-active components, and potential applications coupled to targeted metabolomics - Liu, Zhenying; Cheng, Yunxia; Xiang, Yaoting; Chao, Zhimao (Frontiers in Plant Science, 2024)
The buds of Lonicera japonica Thunb. var. chinensis (Wats.) Bak, commonly named as red honeysuckle, has attracted attention for its bright colors. However, due to the lack of systematically study, its potential application is not clear, and its development and utilization has not been known well. In this study, compared with the buds of Lonicera japonica Thunb. (honeysuckle), the potential applications of red honeysuckle were explored based on biological activities, bio-active components, and sensory flavor combined with widely targeted metabolomics. As a result, in vitro tests showed that it had stronger antioxidant and a stronger inhibitory effect on the growth of Escherichia coli and Staphylococcus aureus. And there was no cytotoxicity on LPS-induced RAW264.7 cells in its aqueous extract by the CCK-8 method. Moreover, it also had a stronger effect on inhibiting the expression of inflammatory factors such as IL-6, TNF-, IL-1. bio-active components chlorogenic acid and cynaroside contents were significantly higher (p ≤ 0.001) than green honeysuckle. Widely targeted metabolomics analysis revealed that 4 volatile metabolites such as (E)-4-hexene-1-ol and pyrazole, and 21 non-volatile metabolites such as macranthoside B and oleanolic acid-3-O-glc(1-2)-(ara)-28-O-glucoside ester were specific in red honeysuckle. Interestingly, 14 specific terpenoids metabolites were triterpenoid saponins, indicating a stronger biological activity in red honeysuckle. The sensory flavor analysis showed that the red honeysuckle had a stronger herbal and lighter floral flavour. In conclusion, red honeysuckle had great development value and potential application in medicines, foods, beverages, pigment additives, and health products.